ALBUMIN SERUM DALAM SIROSIS HATI - Windu Nafika; Leonita Anniwati; Soehartini Soehartini (Indonesian Association of Clinical Pathologist and Medical laboratory, 2013)
Serum albumin measurement can be used for assessing prognosis, determining initial therapy and treatment efficacy for liver cirrhosis patients. The discrepancy result of albumin measurement using different methods can make bias for the albumin concentration. The measurement of albumin was carried out in 20 sera of liver cirrhosis patients using bromcresol green (BCG), BCG conversion as well as bromcresol purple (BCP) methods including protein electrophoresis. The results showed that BCP method has a lower albumin concentration than the other kind (1.68±0.35), BCG (1.94±0.31), BCG conversion (2.09±0.45) as well as protein electrophoresis (2.14±0.35). BCP method has a good correlation with protein electrophoresis as well as BCG conversion (r=0.935 and r=0.90 respectively). It can be concluded in this study, that albumin measurement with BCP method has a good correlation with protein electrophoresis. It is important to know that the measurement results of BCP method is lower but more accurate in the albumin concentration, because there is no cross reaction with globulin. That means, there is no overestimation of albumin concentration in hypoalbuminemia condition of the patients.